Perencanaan Pengelolaan Desa Dunu sebagai Destinasi Wisata Olahraga Paralayang dan Wisata Perkemahan melalui Pemberdaayaan Masyarakat di Kabupaten Gorontalo Utara - Kadir, Poppy Arnold (Ideas Publishing, 2025)
Dunu Village is one of the villages in the North Gorontalo region which has the potential for beach tourism and paragliding sports tourism as well as the potential for camping tourism. Most of the professions of the Dunu people are fishermen and farmers. The life of the Dunu village community only relies on income from marine products and agricultural products, while the tourism potential has not been properly explored. Community-based tourism is a concept for developing tourist villages by involving and placing local communities who have the authority to manage and develop their own areas to improve the welfare of local communities and the sustainability of local culture and natural resources. This research aims to provide input and recommendations for planning strategies for the development and management of tourist destinations in the coastal and hill areas of Dunu Village, Monano District, North Gorontalo Regency using a community empowerment approach. The method used in this research is a qualitative descriptive analysis method. The results of the research are then used as input for planning and developing and managing the tourist area in Dunu Village, namely the strategy for developing and managing the tourist village of Dunu Village which has tourism potential which will be supported by the regional government, village government, academics, business managers and Pokdarwis.